HUBUNGAN STATUS STRES PSIKOSOSIAL DENGAN KONSUMSI MAKANAN DAN STATUS GIZI SISWA SMU METHODIST-8 MEDAN - Tienne A.U Nadeak; Albiner Siagian; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Being a teenager is the period development transition between childhood and adulthood involving biological, cognitive and psychosocial changes. Stress causes eating disorder in the forms of less or increasing appetite and nutritional absorption disorder. The purpose of this quantitative analytical survey study with cross-sectional design was to the relationship between the status of psychosocial stress with food consumption and nutritional status. The samples for this study were 77 students of SMU Methodist 8 Medan. The data about the status of psychosocial stress were obtained through distributing ALCES questionnaire. The data about food consumption were obtained through 2 x 24 hour food recall forms. The data about anthropometry collected were body height and body weight. The data obtained were analyzed through Chi-square test. The result of this study showed that 30 respondents (39%) were with normal nutritional status, 27 respondents (35%) were fat, 11 respondents (14.3%) were thin. It was also found out that 47 respondents (61.0%) were with the status of severe psychosocial stress, 18 respondents (23.4%) with the status of medium psychosocial stress. The result of Chi-square test showed that there was a significant relationship between the status of psychosocial stress and food consumption, between the status of psychosocial stress and nutritional status, and between energy consumption and the students’ nutritional status. It is suggested to reduce the stress status of the students, need to facilitate the development of the talent of the students through sport, art or any other activity. Keywords: Psychosocial Stress, Teenager, Food Consumption, Nutritional Status